(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe knowledge, attitudes, and practices regarding blood exposure prevention among preventive medicine students at Tra Vinh University in 2025. Methods: A cross-sectional study was conducted among 230 preventive medicine students at Tra Vinh University. Data were collected using a structured questionnaire and analyzed using descriptive statistics based on percentage distributions. Results: A total of 30.43% of students reported previous blood exposure during clinical practice, mainly in Internal Medicine (29.0%) and Surgery (24.0%). Regarding knowledge, 80.0% achieved an “adequate” level; 90.0% demonstrated positive attitudes. For practices, 78.7% achieved adequate overall performance, with the highest correct practice in medical waste segregation (91.3%) and the lowest in hand hygiene before and after procedures (21.3%). Reported barriers to compliance included rapid procedures, perceptions that glove use substitutes for handwashing, and beliefs that waste segregation was not part of student responsibilities. Conclusion: Students showed good knowledge and positive attitudes regarding blood exposure prevention; however, certain preventive practices particularly hand hygiene and use of personal protective equipment remain suboptimal and require further strengthening.